2021
DOI: 10.1038/s41598-021-88504-0
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling age-dependent DNA methylation: deterministic, stochastic, and nonlinear

Abstract: DNA methylation variability arises due to concurrent genetic and environmental influences. Each of them is a mixture of regular and noisy sources, whose relative contribution has not been satisfactorily understood yet. We conduct a systematic assessment of the age-dependent methylation by the signal-to-noise ratio and identify a wealth of “deterministic” CpG probes (about 90%), whose methylation variability likely originates due to genetic and general environmental factors. The remaining 10% of “stochastic” Cp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…It was suggested that 90 % of CpG sites are driven by non-stochastic genetic and environmental factors, while only 10 % are driven by biological stochastic variation 43 . Our single-cell simulation results, in contrast, are in line with a recent publication by Tarkhov et al 20 that showed increased single-cell DNA methylation level heterogeneity with age.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that 90 % of CpG sites are driven by non-stochastic genetic and environmental factors, while only 10 % are driven by biological stochastic variation 43 . Our single-cell simulation results, in contrast, are in line with a recent publication by Tarkhov et al 20 that showed increased single-cell DNA methylation level heterogeneity with age.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, we have modelled methylation trajectories linearly. Previous studies of cultured fibroblasts [ 79 ] and cross-sectional human cohorts [ 80 ] suggest non-linear dynamics at some CpGs. Given the number of observations available per individual in the LBC cohort, non-linear trajectories cannot be fitted sufficiently robustly.…”
Section: Discussionmentioning
confidence: 99%
“…When the variability in the DNA methylation intensity changes during aging, the residuals of the fitted regression function are expected to reflect this change. Previous studies have shown age-related increases in the variability of DNA methylation [ 10 , 21 23 ]; however, it is not clear how this variability changes with age. We, therefore, applied the DICNAP to analyze the pattern of variability functions for methylation intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Human phenotype and disease risk also show different patterns of age-related changes [ 5 ], and nonlinear age-related changes in RNA and protein expression have also been reported [ 6 9 ]. For some DNA methylation sites, nonlinear changes in methylation intensity during aging following a power law have been reported [ 10 ]. While the patterns of aging are thought to reflect the underlying biological mechanisms, the overall landscape of nonlinear changes during aging is unknown.…”
Section: Introductionmentioning
confidence: 99%